2005
DOI: 10.1055/s-2005-837578
|View full text |Cite
|
Sign up to set email alerts
|

Representation and High‐Quality Annotation of the Physcomitrella patens Transcriptome Demonstrates a High Proportion of Proteins Involved in Metabolism in Mosses

Abstract: To gain insight into the transcriptome of the well-used plant model system Physcomitrella patens, several EST sequencing projects have been undertaken. We have clustered, assembled, and annotated all publicly available EST and CDS sequences in order to represent the transcriptome of this non-seed plant. Here, we present our fully annotated knowledge resource for the Physcomitrella patens transcriptome, integrating annotation from the production process of the clustered sequences and from a high-quality annotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 56 publications
4
76
0
Order By: Relevance
“…Many such analyses revealed an unexpected variety of enzymes and pathways alternative to those in flowering plants. These observations were corroborated by transcriptome analysis which showed that, whereas in seed plants 10-44% of genes are involved in metabolism, the proportion of metabolic genes in P. patens reaches 70-80% [21]. Analysis of sulfur metabolism in P. patens revealed that some metabolic steps are less complex in this moss than in seed plants, while others are more diverse in mosses [19].…”
Section: Introductionmentioning
confidence: 69%
“…Many such analyses revealed an unexpected variety of enzymes and pathways alternative to those in flowering plants. These observations were corroborated by transcriptome analysis which showed that, whereas in seed plants 10-44% of genes are involved in metabolism, the proportion of metabolic genes in P. patens reaches 70-80% [21]. Analysis of sulfur metabolism in P. patens revealed that some metabolic steps are less complex in this moss than in seed plants, while others are more diverse in mosses [19].…”
Section: Introductionmentioning
confidence: 69%
“…Considering the absence of a second allele which could balance somatic mutations, this drawback is compensated by a high metabolic redundancy (Lang et al 2005), whole genome duplications (Rensing et al 2007), and the arrest of the cell cycle after DNA synthesis in the G2 phase (Schween et al 2003), combined with efficient DNA repair mechanisms such as homologous recombination (Kamisugi et al 2006). …”
Section: Mosses Are Haploid Dominantmentioning
confidence: 99%
“…Thereby, the selection of genes of interest that will be disrupted is based on bioinformatic predictions or experimental indications. Nevertheless, as approximately 1/3 of the P. patens transcripts do not show significant homology to genes from other species (Nishiyama et al, 2003;Lang et al, 2005), there is a particular demand for unbiased forward genetics screens to determine novel gene functions.…”
Section: Forward or Reverse Genetics To Address Biological Questionsmentioning
confidence: 99%